Optogenetic activation of presynaptic inputs in lateral amygdala forms associative fear memory - Kwon, Jeong-Tae; Nakajima, Ryuichi; Kim, Hyung-Su; Jeong, Yire; Augustine, George J.; Han, Jin-Hee (COLD SPRING HARBOR LAB PRESS, PUBLICATIONS DEPT, 2014)
In Pavlovian fear conditioning, the lateral amygdala (LA) has been highlighted as a key brain site for association between sensory cues and aversive stimuli. However, learning-related changes are also found in upstream sensory regions such as thalamus and cortex. To isolate the essential neural circuit components for fear memory association, we tested whether direct activation of presynaptic sensory inputs in LA, without the participation of upstream activity, is sufficient to form fear memory in mice. Photostimulation of axonal projections from the two main auditory brain regions, the medial geniculate nucleus of the thalamus and the secondary auditory cortex, was paired with aversive footshock. Twenty-four hours later the same photostimulation induced robust conditioned freezing and this fear memory formation was disrupted when glutamatergic synaptic transmission was locally blocked in the LA. Therefore, our results prove for the first time that synapses between sensory input areas and the LA, previously implicated as a crucial brain site for fear memory formation, actually are sufficient to serve as a conditioned stimulus. Our results strongly support the idea that the LA may be sufficient to encode and store associations between neutral cue and aversive stimuli during natural fear conditioning as a critical part of a broad fear memory engram.
Keywords: MEDIAL GENICULATE-NUCLEUS; PRIMARY AUDITORY-CORTEX; LONG-TERM POTENTIATION; CONDITIONED FEAR; UNCONDITIONED STIMULUS; INHIBITORY CIRCUITS; SYNAPTIC PLASTICITY; PYRAMIDAL CELLS; NEURAL CIRCUITS; MECHANISMS